Investigation of environmental contamination in lichens of Gökçeada (Imbroz) Island in Turkey - Gurler, Orhan; Kahraman, Ayşegül; Ozturk, Şule; Gundogdu, O.; Yalcin, S.; Kaynak, G. (Elsevier BV, 2009)
Abstract The main objective of the present study is to determine the type of environmental contamination in lichens in Gokceada Island in the Northern Aegean Sea in Turkey. We used two different lichen species Cladonia foliacea and Ramalina pollinaria. In the first part of the investigation, the beta activities of lichens have been measured by using a TENNELEC LB 1000-PW detector. The range of beta activity values was between 607 ± 30 and 308 ± 12 Bq/kg for C. foliacea lichens collected from around Tuz Lake and values for R. pollinaria lichens were found to be 740 ± 25 and 541 ± 17 Bq/kg. The second part of the study was concerned with the gamma spectra of the lichen samples measured by using HpGe detector. 137Cs, 134Cs, 40K, 232Th, 226Ra radionuclides were found in C. foliacea collected from around Tepekoy and in R. pollinaria from around Tuz Lake. When these two types of lichens were compared, it was found that R. pollinaria contain more radionuclides. In order to compare and determine which of these lichens act as a better bioaccumulator, K, Mn, Zn, Rb, Sr, Ba and Pb metal content were determined by using Energy Dispersive X-ray fluorescence spectrometry. It was found that C. foliacea collected more Mn and Sr when compared to R. pollinaria.